Terapi Water Treadmill untuk Penanganan Hip dysplasia pada Anjing Beagle - Shady Jasmin; Frizky Amelia; Zulfa Ichsanniyati; R. Haryy Soehartono; Deni Noviana (IPB University, 2023)
Water treadmill is a modality in veterinary medical rehabilitation belongs to therapeutic exercise with natural muscle stimulation. Water treadmill use advantageous physical properties of water to improve joint flexibility, endurance, balance, and animal posture by increasing muscle mass and strength, range of motion, and reducing pain. Water treadmills are often used to rehabilitate hind limb musculoskeletal problems in dogs with hip dysplasia. Hip dysplasia can occur in all dog breeds including the Beagle. A five year old Beagle, female sex, weighing 14.60 kg came to the Mody Pet's Club and RnD Clinic with complaints of limping and weakness on his hind legs. The results of the physical examination showed the dog was lame with a score of 2/4. The results of the radiographic examination observed moderate degree of hip dysplasia. Measurement of the thigh muscles showed muscle atrophy. The therapy carried out was therapeutic exercise with a water treadmill every week for ten times. The results of the study concluded that water treadmill therapy provided an improvement in the condition of dogs with moderate hip dysplasia to close to mild hip dysplasia.